STRATEGI PENGEMBANGAN KOLEKSI PEPRUSTAKAAN SMP NEGERI 45 BANDUNG - Adiva Khafifati; Angga Hadiapurwa (Departemen Sastra Indonesia, Fakultas Sastra, Universitas Negeri Malang (UM), 2023)
This study aims to find out in depth the collection development strategy of SMP Negeri 45 Bandung Library. This research is qualitative research, using observations, interviews, and literature as data collecting. The results show that the SMP Negeri 45 Bandung library carries out collection development activities in the form of; 1) library collection analysis, 2) selection, 3) library collection acquisition, 4) collection evaluation and collection weeding, of the six components of the collection development process. Libraries should develop policies regarding collection selection and collection evaluation.